P.076 Hypertensive disorders in pregnancy are strongly associated with future stroke and hypertension: A systematic review and meta-analysis. (November 2021) - Switzer, AR; Smith, EE; Ganesh, A
Abstract : Background: We aimed to evaluate the association between hypertensive disorders in pregnancy (HDP) and future risk of stroke, stroke death, and hypertension. Methods: Systematic searches were performed in MEDLINE and EMBASE up to April 27 th, 2020. Exposure of interest included the different types of HDP. Outcomes of interest included hypertension incidence, stroke incidence, stroke subtype, and stroke mortality. Results: Eighteen cohort and 1 case-control studies involving >10 million women were included in the meta-analysis. Pooled hazard ratios with 95% confidence interval generally adjusted for age at delivery, ethnicity, and vascular risk factors are listed in table 1 . Conclusions: Increasing severities of HDP carry higher hazards of hypertension and stroke years later. HDP, including gestational hypertension alone, are also associated with future stroke mortality.